A national‐scale dataset for threats impacting Australia's imperiled flora and fauna. Issue 17 (4th August 2021) - Ward, Michelle; Carwardine, Josie; Yong, Chuan J.; Watson, James E. M.; Silcock, Jennifer; Taylor, Gary S.; Lintermans, Mark; Gillespie, Graeme R.; Garnett, Stephen T.; Woinarski, John; Tingley, Reid; Fensham, Rod J.; et al.
Abstract: Australia is in the midst of an extinction crisis, having already lost 10% of terrestrial mammal fauna since European settlement and with hundreds of other species at high risk of extinction. The decline of the nation's biota is a result of an array of threatening processes; however, a comprehensive taxon‐specific understanding of threats and their relative impacts remains undocumented nationally. Using expert consultation, we compile the first complete, validated, and consistent taxon‐specific threat and impact dataset for all nationally listed threatened taxa in Australia. We confined our analysis to 1, 795 terrestrial and aquatic taxa listed as threatened (Vulnerable, Endangered, or Critically Endangered) under Australian Commonwealth law. We engaged taxonomic experts to generate taxon‐specific threat and threat impact information to consistently apply the IUCN Threat Classification Scheme and Threat Impact Scoring System, as well as eight broad‐level threats and 51 subcategory threats, for all 1, 795 threatened terrestrial and aquatic threatened taxa. This compilation produced 4, 877 unique taxon–threat–impact combinations with the most frequently listed threats being Habitat loss, fragmentation, and degradation ( n = 1, 210 taxa), and Invasive species and disease ( n = 966 taxa). Yet when only high‐impact threats or medium‐impact threats are considered, Invasive species and disease become the most prevalent threats. This dataset provides critical information for conservation action planning, national legislation and policy, and prioritizing investments in threatened species management and recovery. Abstract : Australia is in the midst of an extinction crisis as a result of an array of threatening processes; however, a comprehensive taxon‐specific understanding of threats and their relative impacts remains undocumented nationally. Using expert consultation, we compile the first complete, validated, and consistent taxon‐specific threat and impact dataset for all 1, 796 nationally listed threatened taxa in Australia. This compilation produced 4, 877 unique taxon–threat combinations with the most frequently listed threats being Habitat loss, fragmentation, and degradation ( n = 1, 210 taxa), and Invasive species and disease ( n = 966 taxa).